A rapid method for the extraction and determination of vitamin E metabolites in human urine - John K. Lodge; Maret G. Traber; Angelika Elsner; Regina Brigelius-Flohé (Journal of Lipid Research, 2000)
A method for the direct extraction and routine analysis of the vitamin E metabolites γ- and α-carboxyethyl hydroxychroman (γ- and α-CEHC) from human urine has been developed. A relatively small sample volume (5 ml) can be used and, after enzymatic hydrolysis of the conjugated forms and acidification, the metabolites are extracted with diethyl ether. Recovery of α- and γ-CEHC was compared to that of trolox, used as an internal standard, added to 24-h urine collections from vitamin E-unsupplemented volunteers. Various solvent conditions were initially tested; acidification and ether extraction gave the highest recovery. It was found that after addition and extraction from urine, trolox, α- and γ-CEHC are recovered to a similar extent, hence trolox is viable as an internal standard. The samples were analyzed by both GC and HPLC with electrochemical detection (ECD). HPLC-ECD was found to give higher selectivity and higher sensitivity compared to GC or HPLC with UV detection at 290 nm. The HPLC-ECD detection limit was 10 fmol, linearity (r2 > 0.98) was achieved in the range of 40 to 200 fmol, which was found to be optimal for 24-h urines from unsupplemented subjects. Inter-sample variability was typically 2–5%. This greater sensitivity and selectivity means that vitamin E metabolites can be analyzed even in unsupplemented subjects. It is also possible to measure unconjugated forms of the metabolites. Typically these were found to represent ~10% of the total α- and γ-CEHC. This method can be used routinely for the determination of vitamin E metabolites in urine. The new extraction and detection methods described are relatively quick, less laborious, and more cost-effective than previously available methods. —Lodge, J. K., M. G. Traber, A. Elsner, and R. Brigelius-Flohé. A rapid method for the extraction and determination of vitamin E metabolites in human urine.